Inhibitory effects of AptaminC320 targeting vitamin C on LPS-induced inflammation in RAW264.7 cells - Solip Choi; June Lee; Jeong-Ho Park; Gyuyoup Kim (Biochemistry and Biophysics Reports)
Inflammation, a vital immune response, is regulated by macrophages. Key regulators of this response in macrophages are the nuclear factor-kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) pathways. This study explored the anti-inflammatory effects of vitamin C and AptaminC320 in macrophages. We found that nitric oxide, produced by lipopolysaccharide (LPS), was reduced by vitamin C and AptaminC320 in RAW264.7 cells, which are murine macrophages. Furthermore, these substances reduced the production of inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-6, and interleukin-1β. We also demonstrated that protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), increased by LPS in macrophages, as well as the phosphorylation of c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and p38, were reduced by vitamin C and AptaminC320. These findings suggest that vitamin C and AptaminC320 exhibit anti-inflammatory activity by modulating NF-κB and MAPK signaling, suggesting that they offer significant therapeutic potential as safe and effective treatments for inflammatory diseases with minimal side effects in comparison with the commonly used steroidal anti-inflammatory drug dexamethasone.